Fifteen-minute consultation: Clinical pubertal assessment. Issue 4 (14th May 2021) - Prentice, Philippa
Abstract : A pubertal assessment is an important part of the clinical examination of a young person. Clinicians must be empowered to do this confidently and in a sensitive manner. Tanner staging allows an objective measurement of pubertal status, including pubic and axillary hair growth, and breast or genital development. Alongside history, age and growth patterns, pubertal assessment can identify normal, precocious, delayed or arrested puberty and be suggestive of underlying pathology. This article aims to familiarise clinicians with the pubertal assessment, both the examination and interpretation.